The Extraction Pattern of “Al-Samii“ based on the Contextual Meaning on Makkiy and Madaniy in the Quran - Robiatul Adawiyah Mohd @ Amat; Norzulaili Mohd Ghazali; Abdul Rahman Hussein Obeid; Noornajihan Ja‘afar; Hishomudin Ahmad; Muhammad Widus Sempo; Norwahida Mohamad; Norullisza Khosim; Abdul Karim Toure; Nurul Asiah Fasehah Muhammad (PIMM Experts Sdn Bhd., 2024)
Non-Indexed Publication